Cloning and Characterization of Two Toll Receptors (PcToll5 and PcToll6) in Response to White Spot Syndrome Virus in the Red Swamp Crayfish Procambarus clarkii - Huang, Ying; Chen, Yihong; Hui, Kaimin; Ren, Qian (Frontiers in Physiology, 2018)
Toll/Toll-like receptors are key components in the innate immune responses of invertebrates. In this study, we identified two novel Toll receptors (PcToll5 and PcToll6) from the red swamp crayfish Procambarus clarkii. The complete cDNA sequence of PcToll5 is 4247 bp, encoding a 1293 amino acid polypeptide. The full-length 4688 bp PcToll6 encodes a putative protein of 1195 amino acids. Quantitative RT-PCR analysis indicated that PcToll5 and PcToll6 were constitutively expressed in all tissues studied. The highest expression levels of PcToll5 and PcToll6 were found in the intestine and gills, respectively, and were significantly upregulated from 24 to 48 h during white spot syndrome virus (WSSV) challenge. siRNA-mediated RNA interference results showed that PcToll5 and PcToll6 might regulate the expression of anti-lipopolysaccharide factors (PcALF2 and PcALF3) in vivo. Overexpression of PcToll5 and PcToll6 in Drosophila Schneider 2 (S2) cells activated the transcription of Drosophila antimicrobial peptides, including drosomycin (Drs), metchnikowin (Mtk), and attacin A (AttA), and shrimp Penaeidin-4 (Pen4). These findings provide significant information that PcToll5 and PcToll6 may contribute to host immune defense against WSSV in P. clarkii.